Accra, Ghana, 22-24 November 2006 = Rapport de la quatorzième session du Comité des pêches continentales pour L'Afrique, Accra, Ghana, 22-24 novembre 2006. (Accra, Ghana, 2007)
This document is the report of the fourteenth session of the Committee for Inland Fisheries of Africa (CIFA), which was held in Accra, Ghana, from 22 to 24 November 2006. The major topics discussed were: reports of some intersessional activities; regional dimensions of inland fisheries development; regional dimensions of aquaculture development; role and responsibilities of CIFA; development, use and dissemination of improved seed for aquaculture and proposals for the major topics for discussion at the fifteenth session of CIFA.
Keywords: Fishery policy,Fishery management,Chính sách nghề cá,Quản lý nghề cá; Middle East,Middle East,Trung Đông,Trung Đông